Validation and Reliability of a Novel Vagus Nerve Neurodynamic Test and Its Effects on Heart Rate in Healthy Subjects: Little Differences Between Sexes - Carta, Giacomo; Seregni, Agnese; Casamassima, Andrea; Galli, Manuela; Geuna, Stefano; Pagliaro, Pasquale; Zago, Matteo (Frontiers in Neuroscience, 2021)
Background: The Vagus Nerve (VN) also called pneumogastric nerve connects the brainstem to organs contained in the chest and abdomen. Physiologically, VN stimulation can rapidly affect cardiac activity and heart rate (HR). VN neuropathy can increase the risk of arrhythmias and sudden death. Therefore, a selective test of VN function may be very useful. Since peripheral neurodynamic tests (NDT) are reliable for neuropathies assessment in somatic nerves, we aimed to validate a novel NDT to assess the VN activity, namely the VN-NTD. Methods: In this cross-sectional double-blind, sex-balanced study, 30 participants (15 females) completed a checklist of autonomic dysfunction symptoms. During the VN-NDT administration, HR and symptoms (i.e., mechanical allodynia) were monitored in parallel to a real-time ultrasonography imaging (USI) and motion capture analysis of the neck. The VN-NDT impact on HR and its accuracy for autonomic symptoms reported in the last 7 days was tested. Results: The VN-NDT induced a significant HR reduction of about 12 and 8 bpm in males and females (t[1, 119]= 2.425; p<0.017; ηp2=0.047, 95% confidence interval [CI]: 0.93 – 9.18), respectively. No adverse events were observed during VN-NDT. A substantial inter-examiner agreement between the evaluators in symptoms induction by VN-NDT was detected (F[1, 119]= 0.540;p=0.464; ηp2=0.005, low effect). Notably, mechanical allodynia accuracy for gastrointestinal dysfunctions was excellent (p<0.05; 95% CI:0.52–0.73; p<0.001; 95% CI:0.81–0.96). Conclusions: The novel VN-NDT is a valid and accurate test capable of detecting VN activation with high sensitivity. Data provided are suitable for both sexes as a hallmark of HR variation duet to VN normal response. The proposed VN-NDT may be reliable as daily routine neurological examination tests for the evaluation of neuropathic signs related to neuroinflammation. (NCT04192877)